Autoantibody Frequency in Celiac Disease - Çaǧlar, E.; Uǧurlu, S.; Özenoğlu, A.; Can, G.; Kadioǧlu, P.; Dobrucalı, A. (Hospital Clínicas, Univ Sao Paulo, 2009)
AIM: In our study, we investigated the levels of glutamic acid decarboxylase antibody (anti-GAD), islet cell antibody (ICA), thyroperoxidase antibody (anti-TPO), thyroglobulin antibody (anti-TG), antinuclear antibodies (FANA), antibodies to double-stranded DNA (anti-ds DNA), antibody to Sjögren syndrome A antigen (anti-SSA), antibody to Sjögren syndrome B antigen (anti-SSB), Smith antibody (anti-Sm), smooth muscle antibodies (ASMA), and antimitochondrial antibody liver-kidney microsome (AMALKM) in patients with celiac disease as compared to healthy controls and autoimmune hypothyroid patients. MATERIALS AND METHODS: A total of 31 patients with celiac disease, 34 patients with autoimmune hypothyroidism and 29 healthy subjects were included in this study. Anti-SSA, anti-SSB, anti-Sm, anti-ds DNA, anti-GAD, anti-TPO and anti-TG were studied by Enzyme-Linked Immunosorbent Assay (ELISA), and AMA-LKM, ASMA, ANA and ICA were studied by immunofluorescence. Clinical data and the results of free thyroxine-thyroid stimulating hormone (FT4-TSH) were collected from the patients' files by retrospective analysis. SPSS ver 13.0 was used for data analysis, and the χ2 method was used for comparisons within groups. RESULTS: The frequency of anti-SSA, anti-SSB, anti-GAD, anti-Sm, anti-ds DNA, AMA-LKM, ASMA, ANA and ICA were not significantly different between the groups. Levels of anti-TPO and anti-TG antibodies were found to be significantly higher (<0.001) in autoimmune hypothyroid patients when compared with other groups. CONCLUSION: In previous studies, an increased frequency of autoimmune diseases of other systems has been reported in patients with celiac disease. We found that the frequency of autoimmune antibodies specific for other autoimmune diseases was not higher in celiac disease.
Keywords: Antinuclear Antibodies; Autoimmune Antibodies; Autoimmune Diseases; Autoimmune Hypothyroid Patients; Celiac Disease